THE IMPACT OF THE MBKM PROGRAM ON ENGLISH LANGUAGE EDUCATION STUDY PROGRAM STUDENTS’ SELF-CONFIDENCE IN TEACHING ENGLISH - Melinda, Melinda; Ariyani, Amra; Asriati, Asriati (Universitas Negeri Makassar, 2025)
This research aims to find the impact of the MBKM program on increasing students' confidence in teaching English, focusing on students in the Merdeka Belajar Kampus Merdeka (MBKM), especially the AJARMI program, batch 3, in the English Language Education Study Program, Faculty of Language and Literature, Universitas Negeri Makassar. The study involved a sample of 10 AJARMI students selected through purposive sampling. Using a qualitative approach, data were collected through interviews and analyzed descriptively. The results show that the MBKM program has a positive and significant effects on students' confidence in teaching English. This increase in confidence is evident in various aspects, such as communication skills, classroom management, creating a positive learning atmosphere, the ability to give feedback, student evaluation, and teaching readiness. Furthermore, the program contributes to the development of students' personal behavior in teaching.